Micronuclei and its significance Subject: oral pathology/molecular biology - CHANDINI RAVIKUMAR (International Journal of Pharma and Bio Sciences, 2017)
Micronucleus is conveniently the name given to the small nucleus that forms whenever a chromosome or a fragment of it is not incorporated into one of the daughter nuclei during cell division. It is known to be a sign of chromosomal instability and genotoxic events that are predominantly seen in cancerous cells, and eventually indicate genomic damage to result in degenerative diseases, or diseases of developmental aetiology. The term micronucleus may also be alluded to as the Paramecium, a ciliate protozoan. In earlier studies it stated that the micronucleus induction by a chemical was apparently, first reported in Ehrlich ascites tumour cells that got treated with colchicine. Also, the apparent relationship between formation of micronuclei and exposure to environmental factors was first recognised in root tip cells that got exposed to ionising radiation. It’s formation has been suggested to be observed in cells undergoing nuclear division, that basically results from acentric chromosome fragments that are not included in the daughter nuclei. Several micronucleus tests or assays are performed in which the genotoxicity of chemical compounds are tested. These tests provide important information about a chemical’s ability to interfere with chromosome structure and function. The purpose of this review article is to learn about Micronuclei and its fundamental role in causing oral cancer. The origin, formation and identification, the significance and the different micronucleus assays performed have been described briefly.